1999
DOI: 10.1099/00207713-49-1-319
|View full text |Cite
|
Sign up to set email alerts
|

Zygosaccharomyces lentus sp. nov., a new member of the yeast genus Zygosaccharomyces Barker

Abstract: Unusual growth characteristics of a spoilage yeast, originally isolated from spoiled whole-orange drink and previously identified as Zygosaccharomyces bailii, prompted careful re-examination of its taxonomic position. Smallsubunit rRNA gene sequences were determined for this strain and for four other strains also originally described as 2. bailii but which, in contrast to other strains of this species, grew poorly or not a t all under aerobic conditions with agitation, failed to grow in the presence of 1 YO ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 18 publications
2
29
2
Order By: Relevance
“…Nine species are currently accepted in the genus (Kurtzman, 1998) and recently two new species, Z. lentus (Steels et al, 1999) and Z. kombuchaensis, have been proposed (Kurtzman et al, 2001;Steels et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nine species are currently accepted in the genus (Kurtzman, 1998) and recently two new species, Z. lentus (Steels et al, 1999) and Z. kombuchaensis, have been proposed (Kurtzman et al, 2001;Steels et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the genus Kodamaea Yamada, Suzuki, Matsuda et Mikata was proposed for that species (Yamada et al 1995b). In this study, Kodamaea ohmeri also found in A. florea, showed a strong (Kurtzman and Robnett 1998;Kurtzman et al 2001;Rosa and Lachance 2005;Steels et al 1999). Bootstrap values were calculated from 1,000 replicates, and values below 50% were omitted.…”
Section: Resultsmentioning
confidence: 99%
“…Another related species, Z. mellis is remarkable for extreme osmotolerance and is a spoiling agent of high sugar foods and honey. Physiological characteristics that make Zygosaccharomyces yeasts particularly problematic include their ability to ferment sugar, osmotolerance, resistance to preservatives, formation of heat-resistant ascospores and fructophily (James and Stratford 2003;Steels et al 1999Steels et al , 2002. A previous study (Suezawa et al 2008), using 26S rDNA D1/D2 and ITS sequencing, of the yeasts isolated from miso and soy sauce in Japan revealed two types of Z. mellis.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Following autoclaving, the sugared tea was inoculated with pure cultures of the preceding three strains, either singly or in combination, and incubated at room temperature for several days. Stan-dard fermentation and assimilation tests do not allow reliable separation of the new species from the closely related Zygosaccharomyces lentus [7], so a rapid diagnostic method has been developed that allows their recognition from restriction fragment analysis of a region of the rDNA repeat. Kurtzman and Robnett ([6], unpublished data) showed from analyses of large subunit (26S) rDNA domain D1/ D2 sequences that NRRL YB-4810 represented a new species of Zygosaccharomyces and that NRRL YB-4882 is a strain of Pichia £uxuum (anamorph Candida vini).…”
Section: Introductionmentioning
confidence: 99%